Methuselah Flies 2004
DOI: 10.1142/9789812567222_0008
|View full text |Cite
|
Sign up to set email alerts
|

SELECTION ON STRESS RESISTANCE INCREASES LONGEVITY IN DROSOPHILA MELANOGASTER

Abstract: --Tests for the causal involvement of specific physiological mechanisms in the control of aging require evidence that these mechanisms can be used to increase longevity or reproductive lifespan. Selection for later reproduction in Drosophila has been shown to lead to increased longevity, as well as increased resistance to starvation and desiccation stresses. Selection for increased resistance to starvation and desiccation in Drosophila melanogaster is here shown to lead to increased longevity, indicating that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(79 citation statements)
references
References 11 publications
5
74
0
Order By: Relevance
“…These include screening genetic mutants for longevity phenotypes (Lin et al 1998), overexpression of genes known to enhance antioxidant defense mechanisms (Parkes et al 1998), generational selection studies (Rose et al 1992), and environmental strategies such as drug consumption (e.g., 4-phenylbutyrate; PBA; Kang et al 2002) or caloric restriction (Clancy et al 2002;Mair et al 2003). It is becoming increasingly clear that different genetic and environmental strategies for life extension lead to different patterns of gerontological decline in functional abilities of Drosophila (e.g., flight, locomotion, visuo-motor coordination, memory, and learning).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include screening genetic mutants for longevity phenotypes (Lin et al 1998), overexpression of genes known to enhance antioxidant defense mechanisms (Parkes et al 1998), generational selection studies (Rose et al 1992), and environmental strategies such as drug consumption (e.g., 4-phenylbutyrate; PBA; Kang et al 2002) or caloric restriction (Clancy et al 2002;Mair et al 2003). It is becoming increasingly clear that different genetic and environmental strategies for life extension lead to different patterns of gerontological decline in functional abilities of Drosophila (e.g., flight, locomotion, visuo-motor coordination, memory, and learning).…”
Section: Discussionmentioning
confidence: 99%
“…The wild-type Drosophila has a maximum lifespan of approximately 1.5 to 2 months, aauditory, and memory), and a high homology of genes to other species including mammals (Rose et al 1992;Curtsinger et al 1995;Osiewacz 1997;Parkes et al 1998;Butler 1999;Phillips et al 2000). Fortini et al (2000), for example, have reported that approximately 65 % of human disease genes are conserved in Drosophila (187 of 287 examined).…”
Section: Introductionmentioning
confidence: 99%
“…In experiment 6 we used the following five-fold replicated stocks: "D" selected for desiccation resistance; "C" selected for starvation resistance, and "CO" as controls (Rose et al, 1992). The D, C, and CO lines of flies were derived from the long-lived O populations in 1989.…”
Section: Stocksmentioning
confidence: 99%
“…Specifically, laboratory selection for postponed reproduction in D. melanogaster has produced populations that have postponed aging Rose and Charlesworth, 1980) and lowered reproduction Service, 1989Service, , 1993Service and Fales, 1993;Service and Vossbrink, 1996). Such fruit flies sometimes show a trade-off between stress resistance and early reproduction (Chippindale et al, 1993;Leroi et al, 1994;Rose et al, 1992;Service and Rose, 1985), suggesting a trade-off of energetic reserves between survival and reproduction (Chippindale et al, 1993;Chippindale, 1994;Graves et al, 1992). Furthermore, selection for stress resistance has been shown to increase longevity (Rose et al, 1992;Rose et al, 2004), suggesting that stress resistance is a causal contributor to longevity and postponed senescence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation